Impact of the COVID-19 pandemic on HPV vaccine uptake in a predominantly Hispanic Border Community: A retrospective cross-sectional analysis of the "Tiempo de Vacunarte Program" - Phong Nguyen; Jessica Calderon-Mora; Vishwajeet Singh; Amir Hernandez; Sonya Roy; Jennifer Molokwu (BMC, 2024)
Abstract Background Human Papillomavirus (HPV) is implicated in the pathogenesis of cancer in the cervix, vagina, throat and anogenital region. Although HPV vaccination rates in the Hispanic community have increased owing to public health efforts, the COVID-19 pandemic has brought unique public health challenges and contributed to health inequity in this population. Methods To evaluate the impact of the COVID-19 pandemic on HPV vaccine uptake in a program designed to improve HPV vaccination rate in a predominantly Hispanic community in the border region of Texas (Tiempo de Vacunarte [time to get vaccinated]), we performed a retrospective cross-sectional analysis to evaluate the uptake of the first dose of HPV vaccine series among eligible adolescents and adults before (2016-2019), during (2020-2021), and after the COVID-19 pandemic (2022-2023). Results We observed a decrease in HPV vaccine uptake during the pandemic (69.59% vs. 89.92%) and post-pandemic (76% vs. 89.92%) compared to the pre-pandemic period. After adjusting for confounding factors, the reduction in the odds ratio was more pronounced in the pandemic (OR = 0.091, p < 0.001) and post-pandemic (OR = 0.109, p < 0.001) periods. Conclusion Our findings suggest that the COVID-19 pandemic significantly impacted the uptake of the HPV vaccine in a comprehensive intervention program to increase HPV vaccination in a border community.